Correlation between Energy and Protein Intake with Stunting Incidence in Toddlers - Purba, Nia Feronika; Emilia, Esi; Juliarti, Juliarti; Mutiara, Erli; Harahap, Novita Sari (Sport and Nutrition Journal, 2023)
Stunting is a nutritional problem that occurs in Indonesia. Stunting is a condition of physical growth failure caused by chronic nutritional problems that occur for a long time. This study aimed to determine the relationship between energy and protein intake with the incidence of stunting. This study used a cross-sectional study design with a sample of 41 toddlers. The results obtained were analyzed using the Spearman Rank correlation test and multiple linear regression tests. There is a positive and significant relationship between energy intake and the incidence of stunting, as shown by the correlation coefficient of 0,72 (p-value = 0,00); in other words, the better the nutritional status (not stunting). There is a positive and significant relationship between protein intake and stunting as indicated by a correlation coefficient of 0,79 (p value = 0,00), in other words, the better the nutritional status (not stunting). Based on the results of multiple linear regression tests, a coefficient of determination of R Square = 0,79 was obtained, which means that the variables of energy intake and protein intake affect the incidence of stunting by 79%.